Use of a Mixture of Gases (C2H2 + N2) to Obtain High-strength Molybdenum-based Carbonyl Nitride Coatings - Р’.Рњ. Beresnev; Рћ.V. SobolвЂ™; A.D. Pogrebnyak; S.V. Litovchenko; A.A. Meylekhov; U.S. Nemchenko; V.A. Stolbovoy; N.S. Evtushenko; D.A. Kolesnikov; M.G.Kovaleva; B.A. Mazilin; L.V. Malikov; et al. (Журнал нано- та електронної фізики)
The effect of working pressure and the components correlation of the gas mixture (C2H2+N2) to the elemental and phase compositions, the structure and physical and mechanical characteristics of the vacuum-arc coatings formed based on tungsten are studied. It is shown that for high-temperature application, nitrides are less preferable in comparison with carbides. In the temperature range of deposition 400-550 В°РЎ, the maximum content of nitrogen atoms in the coating does not exceed 1.5 at.% as a result of plasma-chemical reactions with a gas atmosphere composition of 80% C2H2+20% N2. For a composition of 40% C2H2+60% N2, the maximum N/C ratio (in at.%) increases to 10.5% at a maximum pressure of 3п‚ґ10 вЂ“ 3 Torr. The relative content of nitrogen atoms increases with increasing pressure of the mixture. Plasma-chemical reactions during precipitation in a mixture of gases lead to the formation of phases with a nanometer-sized crystallite and a phase composition based on пЃ§-MoC (80% C2H2+20% N2) and пЃ§-MoC and пЃ§-Mo2N phases (with a smaller content of C2H2 (40% C2H2+60% N2) in the gas mixture It is established that the determining factor for increasing the hardness is the working pressure of the gas mixture during deposition. With the greatest pressure of 3п‚ґ10 вЂ“ 3 Torr, when the texture of nanocrystallites of molybdenum carbide (пЃ§-MoC) is formed [100] an ultrahard state with a hardness of 50.5 GPa is achieved.